Caveolin-1/Endothelial Nitric Oxide Synthase Interaction Is Reduced in Arteries From Pregnant Spontaneously Hypertensive Rats - Troiano, Jéssica A.; Potje, Simone R.; Graton, Murilo E.; Gonçalves, Emily T.; Tostes, Rita C.; Antoniali, Cristina (Frontiers in Physiology, 2021)
We have investigated the role caveolae/caveolin-1 (Cav-1) plays in endothelial nitric oxide synthase (eNOS) activation and how it impacts pregnancy-induced decreased vascular reactivity in normotensive (Wistar rats) and spontaneously hypertensive (SHR) rats. Wistar rats and SHR were divided into non-pregnant (NP) and pregnant (P). Nitrite levels were assessed by the Griess method in the aorta and mesenteric vascular bed. In functional studies, arteries were incubated with methyl-β-cyclodextrin (dextrin, 10 mmol/L), which disrupts caveolae by depleting cholesterol, and concentration-response curves to phenylephrine (PE) and acetylcholine (ACh) were constructed. Electronic microscopy was used to determine endothelial caveolae density in the aorta and resistance mesenteric artery in the presence of vehicle or dextrin (10 mmol/L). Western blot was performed to evaluate Cav-1, p-Cav-1, calmodulin (CaM), and heat shock protein-90 (Hsp90) expression. Cav-1/eNOS interaction in the aorta and mesenteric vascular bed was assessed by co-immunoprecipitation. Nitric oxide (NO) generation was greater in arteries from P-groups compared to NP-groups. Dextrin did not change vascular responses in the aorta from P-groups or the number of caveolae in P-groups compared to NP-groups. Compared to NP-Wistar rats, NP-SHR showed smaller number of caveolae and reduced Cav-1 expression. Pregnancy did not alter Cav-1, CaM, or Hsp90 expression in the aorta or mesenteric vascular bed from Wistar rats or SHR. These results suggest that pregnancy does not alter expression of the main eNOS regulatory proteins, but it decreases Cav-1/eNOS interaction. Reduced Cav-1/eNOS interaction in the aorta and mesenteric vascular bed seems to be an important mechanism to increase eNOS activity and nitric oxide production in pregnant normotensive and hypertensive rats.